2022
DOI: 10.46303/jcve.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

STEM Education Practical Work in Remote Classrooms: Prospects and Future Directions in the Post-Pandemic Era

Abstract: Practical work is pivotal for the development of important skills inherent to science, technology, engineering, and mathematics (STEM) education. Through practical work, learners engage in skills that include critical thinking, problem-solving, and inquiry-based learning, which are important outcomes of STEM education. Given the rise in significance of remote learning as reinforced by the COVID-19 pandemic, there is a need to reimagine the facilitation of practical work for learners. This paper uses the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Often referred to as 'laboratory work,' practical work involves various hands-on activities used by teachers in teaching science at both primary and secondary school levels (Akuma & Callaghan, 2019a;Akuma & Gaigher, 2021;Gericke et al, 2023;Kaindume, 2018;Ndoro, 2017;Ntawuhiganayo & Nsanganwimana).Various definitions of practical work have been identified in various studies, even though there had not been a proper definition of science practical work in literature for about a century. Some believe that practical work comprises learners engaging in hands-on experimentation in a laboratory or classroom, while others believe that practical work entails learners engaging in laboratory work or experiments as part of a teaching demonstration (Akuma & Callaghan, 2019a;Akuma & Gaigher, 2021;Tsakeni, 2022;Wei et al, 2019).…”
Section: Science Practical Workmentioning
confidence: 99%
“…Often referred to as 'laboratory work,' practical work involves various hands-on activities used by teachers in teaching science at both primary and secondary school levels (Akuma & Callaghan, 2019a;Akuma & Gaigher, 2021;Gericke et al, 2023;Kaindume, 2018;Ndoro, 2017;Ntawuhiganayo & Nsanganwimana).Various definitions of practical work have been identified in various studies, even though there had not been a proper definition of science practical work in literature for about a century. Some believe that practical work comprises learners engaging in hands-on experimentation in a laboratory or classroom, while others believe that practical work entails learners engaging in laboratory work or experiments as part of a teaching demonstration (Akuma & Callaghan, 2019a;Akuma & Gaigher, 2021;Tsakeni, 2022;Wei et al, 2019).…”
Section: Science Practical Workmentioning
confidence: 99%
“…Researchers have shown that the STEM educational approach has fallen short of its expectations, as there is still a shortage of STEM graduates and professionals (Hillman et al, 2016;Tsakeni, 2022). Moreover, the number of learners choosing STEM careers is declining when the demand for people to fill scientific positions is rapidly increasing (Hillman et al, 2016).…”
Section: The Stem Educational Approachmentioning
confidence: 99%
“…Moore et al (2020) indicated that the facilitation of science practical work can be conducted by teacher demonstrations that are live-streamed or video-recorded, other videos that can be accessed online, and textbooks. Tsakeni (2022), after conducting a systematic review of literature, suggested five instructional strategies to facilitate practical work remotely in science, technology, engineering, and mathematics (STEM) disciplines. The five strategies are: (i) practical work in virtual reality environments, (ii) practical work in remote laboratories, (iii) practical work in augmented reality environments, (iv) the use of take-home do-it-yourself (DIY) practical work kits, and (v) the use of educational robotics to teach practical work.…”
Section: Use Of Technologies To Prepare Preservice Teachersmentioning
confidence: 99%